COMPARISON OF MYOCARDIAL PROTECTION EFFECTS BETWEEN SEVOFLURANE INHALATION ANESTHESIA AND PROPOFOL TOTAL INTRAVENOUS ANESTHESIA IN OFF-PUMP CORONARY ARTERY BYPASS SURGERY: A MULTICENTER STUDY - Muhammad Fajar Sadli; Reza Widianto Sudjud; Muhammad Budi Kurniawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Introduction: This study aimed to compare the myocardial protective effects of sevoflurane and propofol in patients undergoing Off-Pump Coronary Artery Bypass Grafting (OPCAB). Both anesthetic agents are commonly used in cardiac surgery; however, their relative efficacy in myocardial protection remains unclear. Methods: A total of 36 patients scheduled for elective OPCAB surgery were randomly assigned to two groups: 18 patients received sevoflurane, and 18 received propofol as anesthetic agents. Myocardial injury was assessed by measuring serum CK-MB levels at three time points: pre-induction (T0), 10 h post-surgery (T1), and 24 h post-surgery (T2). Left ventricular function was evaluated by measuring the ejection fraction (EF) preoperatively and postoperatively. Hemodynamic parameters (heart rate, mean arterial pressure, and central venous pressure) were monitored throughout the surgery. Postoperative recovery was assessed by measuring the duration of mechanical ventilation, ICU stay, and hospital stay. Statistical comparisons were made using appropriate tests (t-test, Mann-Whitney, and chi-square) with significance set at p < 0.05. Results: No significant differences were found in CK-MB levels between the sevoflurane and propofol groups at any of the three time points (T0, T1, and T2), indicating equivalent myocardial protection in both groups. The mean CK-MB values at T0, T1, and T2 were comparable between the sevoflurane (19.61 ± 88.081, 74.83 ± 70.503, 49.06 ± 44.421, respectively) and propofol groups (21.72 ± 10.532, 56.28 ± 32.807, 49.00 ± 29.019, respectively). Similarly, ejection fraction values were similar between the two groups preoperatively (sevoflurane: 50.01 ± 14.907%, propofol: 52.67 ± 13.676%) and postoperatively (sevoflurane: 50.72 ± 12.027%, propofol: 49.72 ± 12.136%). The hemodynamic parameters (heart rate, mean arterial pressure, and central venous pressure) were stable and comparable between the groups. Postoperative recovery outcomes, including mechanical ventilation duration, ICU stay, and hospital stay, were similar between the two groups. Conclusion: Sevoflurane and propofol provided equivalent myocardial protection during OPCAB surgery. These findings suggest that either anesthetic agent can be safely and effectively used for anesthesia management in OPCAB procedures without significant differences in myocardial injury or cardiac function.